Clinical outcomes of head and neck adenoid cystic carcinoma patients treated with pencil beam-scanning proton therapy. (August 2020) - Pelak, Maciej J.; Walser, Marc; Bachtiary, Barbara; Hrbacek, Jan; Lomax, Anthony J.; Kliebsch, Ulrike L.; Beer, Jürgen; Pica, Alessia; Malyapa, Robert; Weber, Damien C.
Highlights: Pencil beam scanning proton therapy (PBS PT) in adenoid cystic carcinoma provides a 2-year local control rate exceeding 90%. PBS PT is well tolerated by the patients as no late grade 4–5 late toxicities were observed. Local failure is more likely to occur in elderly patients. There is no significant survival advantage between operated and inoperable patients. Abstract: Objective: The aim of this study was to evaluate the outcome of patients with head and neck adenoid cystic carcinoma (ACC) treated using pencil beam scanning proton therapy (PBS PT) at our institution. Materials and methods: Thirty-five patients who underwent treatment with PBS PT for ACC between 2001 and 2017 were included. Local control (LC), distant control (DC), progression-free survival (PFS), overall survival (OS) and their prognostic factors were evaluated. Adverse effects were prospectively assessed. Results: The median patient follow-up was 30 months. Prior to PT, 26 patients (74.3%) underwent surgery with R0/R1/R2 outcome in 5, 13 and 8 cases, respectively. Nine patients (25.7%) presented with inoperable disease. The 2-year LC, DC, PFS and OS was 92.2%, 77.8%, 74.3% and 88.8%, respectively. LC was influenced by patient age (p = 0.002) with a significant difference between local and distant failure (median 61.3 vs. 42.3 years, p = 0.005). Tumor T stage was a significant risk factor for PFS (p = 0.045) and tumor prognostic group affected OS (p = 0.049). No significant survival advantage for operable vs. inoperable disease could be identified. The acute and late grade 3 toxicity rates were 14.3% and 6.1%, respectively. No acute or late grade 4/5 toxicities were observed. Conclusions: PBS PT is an effective and safe treatment for patients with head & neck ACC in both definitive and adjuvant setting. Distant metastases are the main pattern of failure. Age, tumor stage and clinical stage had a significant negative impact on LC, OS and PFS.